Flosse appeals tribunal ruling lifting Radio Tefana ban - Marie Bopp (Asia Pacific Network, 1999)
French Polynesia's president Gaston Flosse has appealed against a decision by the territory's Administrative Tribunal in a bid to keep pro-independence journalists out of government press conferences.